Hubungan riwayat ibu hamil anemia dengan berat badan dan panjang badan lahir bayi - Mustika, Sandya Windu; Muwakhidah, Muwakhidah; Rakhma, Luluk Ria (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Prevalence of pregnant women with anemia in 2013 was 37.1% and in 2018 it increased to 48.9%. In addition, as many as 51% of pregnant women experience anemia before giving birth. Anemia in pregnant women increases the risk of disorders in fetal development which is a factor influencing the weight and length of the baby at birth. Purpose: To determine the relationship between a history of anemia in pregnant women and the baby's birth weight and length. Method: Analytical study research with a cross-sectional study approach using consecutive sampling. The population of this study were mothers who gave birth at the Bringin Health Center, Ngawi Regency. This study was conducted in October, November, and December 2024 with a sample size of 37 respondents. Data analysis used in testing the relationship and strength between variables is the Chi Square Test statistical test with a degree of confidence p <0.05. Results: Pregnant women with hemoglobin levels who experience anemia are 12 respondents (32.4%). The results of the analysis of the relationship between anemia and birth weight obtained a value of p = 0.003 (<0.05). Mothers with anemia have a 7.29x greater risk of giving birth to a LBW baby. In addition, the relationship between anemia and birth length of the baby shows a relationship between the two variables (p = 0.013) and mothers with anemia have a 6.25x greater risk of giving birth to a short baby. Conclusion: There is a relationship between anemia in pregnant women and the birth weight and length of the baby. Suggestion: Pregnant women are expected to consume foods with high iron content. Keywords: Anemia; Birth Length; Birth Weight; Pregnancy. Pendahuluan: Prevalensi ibu hamil dengan anemia tahun 2013 sebesar 37.1% dan tahun 2018 mengalami peningkatan menjadi 48.9%. Selain itu, sebanyak 51% wanita hamil mengalami anemia sebelum melahirkan. Anemia pada ibu hamil memperbesar resiko gangguan terhadap perkembangan janin yang merupakan faktor pengaruh berat dan panjang bayi saat dilahirkan. Tujuan: Untuk mengetahui hubungan riwayat ibu hamil anemia dengan berat badan dan panjang lahir bayi. Metode: Penelitian analitik dengan pendekatan cross sectional menggunakan consecutive sampling. Populasi penelitian ini ialah ibu yang melahirkan di Puskesmas Bringin Kabupaten Ngawi. Penelitian ini dilakukan pada bulan Oktober-Desember 2024 dengan jumlah sampel yang digunakan sebanyak 37 responden. Analisis data yang digunakan adalah uji statistik Chi Square Test dengan derajat kepercayaan p<0.05. Hasil: Ibu hamil dengan kadar hemoglobin yang mengalami anemia sebanyak 12 responden (32.4%). Hasil analisis hubungan antara anemia dengan berat badan lahir bayi memperoleh nilai p 0.003 (<0.05). Ibu dengan anemia memiliki resiko 7.29x lebih besar melahirkan bayi BBLR. Selain itu, hubungan anemia dengan panjang badan lahir bayi, menunjukkan adanya hubungan antara kedua variabel (p = 0.013) dan ibu dengan anemia memiliki resiko 6.25x lebih besar melahirkan bayi pendek. Simpulan: Ada hubungan antara ibu hamil anemia dengan berat badan dan panjang badan lahir bayi. Saran: Ibu hamil diharapkan konsumsi makanan dengan sumber zat besi yang tinggi. Kata Kunci: Anemia; Berat Badan Lahir; Kehamilan; Panjang Badan Lahir.